Corporate governance and firm’s financial performance amongst private business enterprises in Uganda, a perspective from Lira City - Eton, Marus; Fabian, Mwosi; Arthur, Sunday; Sammy, Godfrey Poro (African Journal of Business Management, 2021)
The study examined the effect of corporate governance on firm’s financial performance amongst private business enterprises in Uganda. The study used descriptive and survey design. A mixed method approach which involved both qualitative and quantitative techniques were also used. The study found out that corporate governance significantly influences the financial performance of hotels and manufacturing firms in Lira City and majority of the firms investigated performed on average financially. It was also established that firms whose boards demonstrate high integrity were likely to register positive changes in their financial performance than firms whose boards do not. The study also noted that board independence would propel the firm to grow to greater heights. The study recommends that hotel and manufacturing firm owners should exercise some discipline and leave boards to operate independently. This would allow the board to remain focused on the long-term goals of the firm. The hotel and manufacturing firm owners should be cautious in selecting board members lest they attract many that would increase the firm’s liabilities.